Numerical Investigation on the Intraphase and Interphase Mass Transfer Limitations for NH3-SCR over Cu-ZSM-5 - Shiyong Yu (MDPI AG, 2021)
A systematic modeling approach was scrutinized to develop a kinetic model and a novel monolith channel geometry was designed for NH3 selective catalytic reduction (NH3-SCR) over Cu-ZSM-5. The redox characteristic of Cu-based catalysts and the variations of NH3, NOx concentration, and NOx conversion along the axis in porous media channels were studied. The relative pressure drop in different channels, the variations of NH3 and NOx conversion efficiency were analyzed. The model mainly considers NH3 adsorption and desorption, NH3 oxidation, NO oxidation, and NOx reduction. The results showed that the model could accurately predict the NH3-SCR reaction. In addition, it was found that the Cu-based zeolite catalyst had poor low-temperature catalytic performance and good high-temperature activity. Moreover, the catalytic reaction of NH3-SCR was mainly concentrated in the upper part of the reactor. In addition, the hexagonal channel could effectively improve the diffusion rate of gas reactants to the catalyst wall, reduce the pressure drop and improve the catalytic conversion efficiencies of NH3 and NOx.